The Grammar Translation Method in Teaching Structure and Written Expression of TOEFL ITP: Is It Still Effective in Today Era? - Prasetya, Angga Eka; Asyhar , Wildan Isna; Muchyidin , M Syaichul (PANYONARA: Journal of English Education, 2024)
The grammar translation method (GTM) is an "ancient" method, and many say that its use is less effective in improving English language skills, especially speaking. However, nowadays, there is an English language certification test known as TOEFL ITP, which is widely used in the educational and professional world where the test does not contain a speaking ability test but rather a test related to the application of grammar called Structure and Written Expression questions. Because GTM was initially an effective method used to learn grammar, researchers tested whether GTM could also be effective in teaching Structure and Written Expression of TOEFL preparation material, which is a test intended for non-English speakers. The method used in this research was quasi-experimental, with two different treatments for each experimental and control class. The findings were analyzed using the paired sample t-test and independent sample t-test calculation methods, and the descriptive test results in each class were compared. The results showed that using GTM can effectively increase students' TOEFL scores in the Structure and Written Expression section, and this has a positive impact on teaching staff to apply the same method to EFL students who plan to take the English language test, namely TOEFL.